Strengthening health systems to tackle oral diseases in Africa: Africa centers for disease control and prevention’s role - Foláyan, Moréniké Oluwátóyìn; Ishola, Adeyinka Ganiyat; Bhayat, Ahmed; El Tantawi, Maha; Ndembi, Nicaise (Frontiers in Public Health, 2025)
Oral diseases remain a significant public health challenge in Africa. Despite their prevalence, oral health is often overlooked in national health agendas and universal health coverage frameworks. This manuscript explores the crucial role of the Africa Centers for Disease Control and Prevention (Africa CDC) in strengthening health systems to address the growing oral health problem in Africa. A rapid review of the literature was conducted in databases like PubMed and ScienceDirect identified 18 relevant studies focusing on workforce size, retention, distribution, patient access, and system outcomes. The analysis revealed severe workforce shortages, uneven distribution, and systemic neglect, particularly in rural areas. Promising interventions included dental education programs, task-shifting to mid-level workers, and mobile dental units. Key recommendations emphasize integrating oral health into national policies, addressing inequities, expanding training, and improving infrastructure and workforce retention through incentives. By leveraging its position and resources, the Africa CDC can take strategic actions to strengthen surveillance and data-driven policy development, provide technical assistance to Africa Union Member States for health system integration, support capacity building for oral health workforce development, promote preventive and community-based oral health interventions, facilitate cross-border collaboration and knowledge sharing, mobilize resources and funding for oral health programs, and support the local production of oral health products. These all aligns with the institution’s new public health order for Africa’s health security and one of the institutions’ 2023–2027 goals.